Timing of renal replacement therapy does not influence survival and growth in children with congenital nephrotic syndrome caused by mutations in NPHS1: data from the ESPN/ERA-EDTA Registry - Hölttä, Tuula; Bonthuis, Marjolein; Van Stralen, Karlijn J.; Bjerre, Anna; Topaloglu, Rezan; Ozaltin, Fatih; Holmberg, Christer; Harambat, Jerome; Jager, Kitty J.; Schaefer, Franz; Groothoff, Jaap W. (Pediatric nephrology, 2016)
Congenital nephrotic syndrome (CNS) of the Finnish type, NPHS1, is the most severe form of CNS. Outcomes of renal replacement therapy (RRT) in NPHS1 patients in Europe were analysed using data from the ESPN/ERA-EDTA Registry. As NPHS1 is most prevalent in Finland and the therapeutic approach differs from that in many other countries, we compared outcomes in Finnish and other European patients.